1995
DOI: 10.1007/bf00373903
|View full text |Cite
|
Sign up to set email alerts
|

Localization and regulation by steroids of the ?, ? and ? subunits of the amiloride-sensitive Na+ channel in colon, lung and kidney

Abstract: Polyclonal antibodies have been raised against the alpha, beta and gamma subunits of the amiloride-sensitive Na+ channel. The three subunits were detected by immunohistochemistry at the apical membrane of epithelial cells from the distal colon, the lung and the distal segments of the kidney tubules. No significant labelling was detected in lung alveoli, suggesting that it is not a major site of expression of the Na+ channel. Effects of a low Na+ diet or of dexamethasone treatment were measured at the mRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
161
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(177 citation statements)
references
References 28 publications
15
161
1
Order By: Relevance
“…Previous studies have found no clear corticosteroid regulation of ENaC or in rat kidney (Renard et al 1995, Asher et al 1996, Escoubet et al 1997, Stokes & Sigmund 1998. These effects on ENaC , and especially , mRNA expression were relatively small and limited to specific renal regions, and thus would probably not have been seen in analyses of the whole kidney.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies have found no clear corticosteroid regulation of ENaC or in rat kidney (Renard et al 1995, Asher et al 1996, Escoubet et al 1997, Stokes & Sigmund 1998. These effects on ENaC , and especially , mRNA expression were relatively small and limited to specific renal regions, and thus would probably not have been seen in analyses of the whole kidney.…”
Section: Discussionmentioning
confidence: 85%
“…Previous work has examined kidney expression of ENaC in the rat (Renard et al 1995, Asher et al 1996, Escoubet et al 1997, Stokes & Sigmund 1998, with modest upregulation of ENaC being reported. However, mineralocorticoid doses used in those rat studies were largely in the pharmacological range (5-to 15-fold greater) (Renard et al 1995, Asher et al 1996, Stokes & Sigmund 1998. In the present study, an upregulation of the level of ENaC mRNA of equal degree was seen across physiological changes in circulating aldosterone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat kidney, message for all three subunits is expressed constitutively and changes little with salt restriction (42). Other investigators described modest changes primarily in ␣ subunit mRNA in rat kidney in response to steroid stimulation or adrenalectomy (42,43).…”
Section: Figmentioning
confidence: 99%
“…8 -10 In contrast, in the kidney, aldosterone affects only the expression of ␣-subunit transcript or protein, 9,11,12 although some investigators found no effect of this hormone on subunit abundance. 4,8,13 Moreover, transgenic mice lacking the mineralocorticoid receptor exhibit a normal abundance of mRNAs encoding ENaC subunits in the kidney. 14 These observations suggest that factors other than aldosterone are involved in the regulation of ENaC in the kidney.…”
mentioning
confidence: 99%